2020
DOI: 10.1124/mol.119.119271
|View full text |Cite
|
Sign up to set email alerts
|

Fentanyl-Induced Block of hERG Channels Is Exacerbated by Hypoxia, Hypokalemia, Alkalosis, and the Presence of hERG1b

Abstract: Introduction: 690 Discussion: 1481 Abbreviations: ANOVA, analysis of variance; APD, action potential duration; FBS, fetal bovine serum; HEK, human embryonic kidney; hERG, human ether a-go-go related gene; IC 50 , half maximal inhibitory concentration; I hERG , hERG current; I Kr , rapidly activating delayed rectifier potassium current; [K + ] o , extracellular potassium concentration; LQTS, long QT syndrome; MEM, minimum essential medium; S.D., standard deviation; τ f-deact , fast time constant of deactivation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…The authors also demonstrated that block by N-methyl-verapamil, a permanently charged analogue of verapamil, was not sensitive to changes in pH, confirming that the effect on block was specifically due to the charge on the drug molecule (Zhang et al 1999 ). Similar explanations have also been posed for other drugs such as flecainide (Du et al 2011 ), ibogaine (Thurner et al 2014 ), fentanyl (Tschirhart and Zhang 2020 ) and hydroxychloroquine (TeBay et al 2021 ) supporting the case that this is a common mechanism for the effect of pH on a drug’s potency to bock ERG.…”
Section: Acidosis and Alkalosismentioning
confidence: 60%
See 2 more Smart Citations
“…The authors also demonstrated that block by N-methyl-verapamil, a permanently charged analogue of verapamil, was not sensitive to changes in pH, confirming that the effect on block was specifically due to the charge on the drug molecule (Zhang et al 1999 ). Similar explanations have also been posed for other drugs such as flecainide (Du et al 2011 ), ibogaine (Thurner et al 2014 ), fentanyl (Tschirhart and Zhang 2020 ) and hydroxychloroquine (TeBay et al 2021 ) supporting the case that this is a common mechanism for the effect of pH on a drug’s potency to bock ERG.…”
Section: Acidosis and Alkalosismentioning
confidence: 60%
“…Here we will focus on studies that have specifically addressed potassium dependence of a drug’s potency to block hERG. Across the literature, reports of the influence of K + on potency to block hERG across drugs is broadly consistent, with increasing extracellular potassium reducing the potency of block (Barrows et al 2009 ; Busch et al 1998 ; Lin et al 2007 , 2008 , 2005c ; Lin and Papazian 2007 ; Mergenthaler et al 2001 ; TeBay et al 2021 ; Wang et al 1997 ; West et al 1997 ; Yang et al 2004 ) and decreased potassium concentration increasing potency of block (Lin et al 2005a ; TeBay et al 2021 ; Tschirhart and Zhang 2020 ). Two potential mechanisms have been proposed to explain this.…”
Section: Effect Of Kalaemic Variation On Drug-induced Long Qt Syndromementioning
confidence: 97%
See 1 more Smart Citation
“…Congenital diseases may eventually manifest during adulthood in response to specific stresses, remaining undiscovered until a dramatic or fatal episode occurs, even in agonistic athletes routinely submitted to ECG to practice [102][103][104][105][106][107][108][109][110][111]. Acquired rhythm pathologies might be induced by several causes, among which drug cardiotoxicity, cardiomyopathies, myocarditis or systemic infections, valve diseases, and interventional/surgical maldeployment of cardiac valve replacements [112][113][114][115][116][117][118][119][120][121][122][123][124][125][126][127][128].…”
Section: Heart Rhythm Diseases: Clinical Signs Underlying Causes and Modeling Approachesmentioning
confidence: 99%
“…Eacret et al focus on the relationship between sleep and opioids, and outline the mechanisms underlying the reciprocal feed-forward interaction between these sleep disruption and opioid use (Eacret et al, 2020). Interestingly, some synthetic opioids might also act outside of opioid receptors, as shown by Tschirhart and Zhang in their study that described how metabolic changes can potentiate the inhibition of specific potassium channels by fentanyl (Tschirhart and Zhang, 2020).…”
Section: Significance Statementmentioning
confidence: 99%